Alarming Carrier Status Of Methicillin Resistant Staphylococcus Aureus (Mrsa) Among Adolescent Learners- Prevalence And Antibiotic Susceptibility Of The Organism - Panneer Selvam (Zenodo, 2018)
Methicillin Resistant Staphylococcus aureus (MRSA) is a well established bacterial pathogen of human beings and is reported as a cause of a number of common diseases both in developed and developing countries. Against the fact that the disease burden is moving in logarithmic phase across the globe, the carriage of MRSA (carrier status) by healthy persons further aggrandizes the issue. In this background, a study has been carried out so as to bring out the real-time carrier status (prevalence) of Staphylococcus aureus and MRSA especially among adolescent healthy learners of higher education in the region. The antibiotypes by standard antibiotic susceptibility tests also have been ascertained. The study concluded that while a total of 43.94% (n= 272) S. aureus of the study was found to be carried by healthy adolescent persons, a total of 20.22% (55 of 272) them was determined to be oxacillin resistant-MRSA. Conclusively, the prevalence of carriage of S. aureus and MRSA is alarming among the target group. : {"references": ["Bassetti, S. Lea Wolfisberg, Barbara Jaussi, R.N., Reno Frei, Marcus F. Kuntze, Manuel Battegay, 2004. Andreas F. Widmer, Carriage of Staphylococcus aureus among injection drug users: lower prevalence in an injection heroin maintenance program than in an oral methadone program. Infect. Control Hosp. Epidemiol. , 25, 133-137..", "Brown, D.F.J., Hawkey, P.M., Edwards, D.I., Morrison, D., Ridgway, G.L., Towner, K.J. and Wren, M.W., 2005. Guidelines for the laboratory diagnosis and susceptibility testing of Methicillin Resistant Staphylococcus aureus (MRSA). J. Antimicrob. Chemother., 56, 1000- 1018.", "CLSI (Clinical and Laboratory Standards Institute), 2007 Performance Standards for Antimicrobial Susceptibility Testing. Wayne, 27(1), M100-S17.", "Collee, J.G., Fraser, A.G., Marmion, B.P., Simmons, A. (eds), 1996. Mackie and McCartney Practical Medical Microbiology, 14th edition. Churchill Livingstone, New York, pp. 131-149.", "Dar, J.A., Thoker, M.A., Khan, J.A., Ali, A., Khan, M.A., Rizwan, M., Bhat, K.H., Dar, M.J., Ahmed, N., Ahmad, S., 2006. Molecular epidemiology of clinical and carrier strains of methicillin resistant Staphylococcus aureus (MRSA) in the hospital settings of north India. Ann. Clin. Microbiol. Antimicrob., 14(5), 22.", "Enright, M.C., Robinson, D.A., Randle, G., Feil, E.J., Grundmann, H. and Spratt, B.G., 2002. The evolutionary history of methicillin resistant Staphylococcus aureus (MRSA). Proc. Natl. Acad. Sci. USA, 99, 7687-7692.", "Goslings, W.R. and Buchli, K., 2001. Nasal carrier rate of antibiotic resistant. Emerg. Infect. Dis., 7, 242-244.", "Hardy, K.J., Hawkey, P.M., Gao, F.and Oppenheim, B.A., 2004. Methicillin resistant Staphylococcus aureus in the critically ill. Br. J. Anaesth,. 56, 121-30.", "Kluytmans, J., Van Belkum, A. and Verbrugh, H., 1997. Nasal carriage of Staphylococcus aureus epidemiology, underlying mechanisms and associated risks. Clin. Microbiol. Rev., 10, 505-520.", "Korn, G.P., Martino, M.D., Mimica, L.J., Chiavone, P.A., Musolino, L.R., 2000. Hih frequency of colonization and absence of identifiable risk factors for methicillin resistant Staphylococcus aureus (MRSA) in intensive care units in Brazil. Braz. J. Infect. Dis., 5, 1-7.", "Kuroda, M., Ohta, T., Uchiyama, I., Baba, T., Yuzawa, H., Kobayashi, I., Cui, L., Oguchi, A., Aoki, K., Nagai, Y., Lian, J., Ito, T., Kanamori, M., Matsumaru, H., Maruyama, A., Murakami, H., 2001. Whole genome sequencing of meticillin-resistant Staphylococcus aureus. Lancet, 357(9264), 1225-1240.", "Mason, W.J., Blevins, J.S., Beenken, K., Wibowo, N., Ojha, N., Smeltzer, M.S., 2001. Multiplex PCR protocol for the diagnosis of staphylococcal infection. J. Clin. Microbiol., 39, 3332-3338.", "Mulla, S., Patel, M., Shah, L. and Vaghela, G., 2007. Study of antibiotic sensitivity pattern of methicillin-resistant Staphylococcus aureus. Indian J. Crit. Care Med., 11(2), 99-101.", "Oslen, K., Falch, B.M., Danielsen, K., Wilsgaard, T., Sangvik, M., Sollid, J.U.E., Thune, I., Grimnes, G., Jorde, R., Simonsen, G.S. and Furberg, A.S., 2012. Staphylococcus aureus nasal carriage is associated with serum 25-hydroxyvitamin D levels, gender and smoking status. The Tromso Staph and Skin Study. Eur. J. Clin. Microbiol. Infect. Dis., 31(4), 465-475.", "Payne, M.C., Wood, H.F., Karakawa, W. and Gluck, L., 1966. A prospective study of Staphylococcal colonization and infections in new borns and their families. Am J. Epidemiol., 82, 05-16.", "Rajaduraipandi, K., Mani, K.R., Panneerselvam, K., M., Bhaskar, M. and Manikandan, P. 2006. Prevalence and antimicrobial susceptibility pattern of methicillin resistant Staphylococcus aureus: a multicentre study. Indian J. Med. Microbiol., 24, 34-38.", "Shapiro, A.R., Raman, S., Johnson, M., and Piehl, M., 2009. Community acquired MRSA infections in North Carolina children: Prevalence, antibiotic sensitivities and risk factors. N. C. Med. J., 70: 102-107.", "Shehabel-Din, S.A., El-Hadidy, M., Bahaa El-Din, A., El- Hadidy, M. and Zaghloul, H., 2001. Methicillin resistant Staphylococcus aureus: a problem in the burns unit. Egypt J. Plast. Reconstr. Surg., 27,1-10.", "Sherertz, R.J., Bassetti, S. and Bassetti-Wyss, B., 2001. \"Cloud\" health-care workers. Emerg. Infect. Dis., 7(2), 241-244.", "Silvana, M., Emmanuel, R. and Carlos, C., 2005. Prevalence of Staphylococcus aureus introduced into intensive are units of a university hospital. Braz. J. Infect. Dis., 9: 1-12."]}